1985
DOI: 10.2166/wst.1985.0132
|View full text |Cite
|
Sign up to set email alerts
|

An Equalization Control Strategy for Activated Sludge Process Control

Abstract: Fluctuations in hydraulic and organic loads cause wastewater treatment plant operating problems, necessitating some form of process control to ensure attainment of design objectives. A comparison of in–plant control with equalization control indicates that the latter is more appropriate for the case of long sludge age nutrient removal activated sludge processes which include anaerobic, anoxic and aerobic zones. A microprocessor-based control strategy is presented for the operation of an equalization tank upstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The issues have been discussed by several workers in the past (for example, Dold et al 1984 andDi Toro 1975) and suggest some sort of predictive model is required for adequate equalization operation. The objective of the work in this paper is to set forth an approach that will provide adequate equalization using a relatively straightforward methodology to equalize high ammonia sidestream returns that could be implemented by operators skilled with the use of spreadsheets.…”
Section: Equation 1: Centrate Tank Outflow (Gpd) = Total Centrate Volmentioning
confidence: 99%
“…The issues have been discussed by several workers in the past (for example, Dold et al 1984 andDi Toro 1975) and suggest some sort of predictive model is required for adequate equalization operation. The objective of the work in this paper is to set forth an approach that will provide adequate equalization using a relatively straightforward methodology to equalize high ammonia sidestream returns that could be implemented by operators skilled with the use of spreadsheets.…”
Section: Equation 1: Centrate Tank Outflow (Gpd) = Total Centrate Volmentioning
confidence: 99%
“…The influent flow and load rate patterns are not identical, but there are interrelations between the two. Thus, no constant output value can be expected simultaneously for both parameters over the daily cycle (Dold et al 1984). Also the diurnal cyclic influent flow and load rate patterns are not repeated identically from day to day.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, equalization as a control tool has been underestimated for several reasons. Dold et al (1984) reported that incorrect parameters have been used to assess the effectiveness of equalization, studied plants were operated at short sludge ages (< 3 days) where equalization could demonstrate little benefit, load equalization has not been considered and studied settling tanks were considerably overloaded. In recent years, as effluent standards have become more stringent and BNR process has gained popularity, equalization applications have been under investigation again.…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuations in hydraulic and organic loads cause wastewater treatment plant operating problems such as aeration control, settling tank overloading, etc. Dold et al (1984) emphasised that the flow and load equalisation can demonstrate full benefits only in plants where sludge age is long and the process includes anaerobic, anoxic and aerobic zones. Equalisation will, in this case simplify, or reduce the control requirements within the plant.…”
Section: Introductionmentioning
confidence: 99%